X-ray properties of He ii λ 1640 emitting galaxies in VANDELS. Issue 3 (23rd June 2020) - Saxena, A; Pentericci, L; Schaerer, D; Schneider, R; Amorin, R; Bongiorno, A; Calabrò, A; Castellano, M; Cimatti, A; Cullen, F; Fontana, A; Fynbo, J P U; et al.
ABSTRACT: We explore X-ray emission from a sample of 18 He ii λ1640 emitting star-forming galaxies at z ∼ 2.3–3.6 from the VANDELS survey in the Chandra Deep Field South, to set constraints on the role of X-ray sources in powering the He ii emission. We find that 4 He ii emitters have tentative detections with S/N ∼ 2 and have X-ray luminosities, LX = 1.5−4.9 × 10 41 erg s −1 . The stacked luminosity of all 18 He ii emitters is 2.6 × 10 41 erg s −1, and that of a subset of 13 narrow He ii emitters (FHWM(He ii ) < 1000 km s −1 ) is 3.1 × 10 41 erg s −1 . We also measure stacked LX for non-He ii emitters through bootstrapping of matched samples, and find LX = 2.5 × 10 41 erg s −1, which is not significantly different from LX measured for He ii emitters. The LX per star formation rate for He ii emitters (log ( LX /SFR) ∼ 40.0) and non-emitters (log ( LX /SFR) ∼ 39.9) are also comparable and in line with the redshift evolution and metallicity dependence predicted by models. Due to the non-significant difference between the X-ray emission from galaxies with and without He ii, we conclude that X-ray binaries or weak or obscured active galactic nuclei are unlikely to be the dominant producers of He ii ionizing photons in VANDELS star-forming galaxies at z ∼ 3. Given the comparable physical properties of both He ii emitters and non-emitters reported previously, alternative He ii ionizing mechanisms such as localized low-metallicity stellar populations, Pop-III stars, etc. may need to be explored.